Differentiated Learning to Improve Student Learning Outcomes in Islamic Religious Education Subjects in Grade VII at SMPN 35 (Boarding) Kaur in the 2024/2025 Academic Year - Azis (Journal of Islamic Pedagogy and Educational Development, 2025)
Background: This study aims to improve student learning outcomes in Islamic Religious Education subjects. This study uses differentiated learning that is currently developing in the world of education, especially in the current Independent Curriculum, which involves three elements, namely visual, auditory, and kinesthetic. Method: This research is a classroom action research that is divided into two cycles and begins with a pre-cycle. Each cycle consists of planning, implementing actions, observation, evaluation, and reflection. The research was conducted on grade VII students in the first semester (odd) at SMPN 35 (Boarding) Kaur in the 2024/2025 academic year. Results: The results of the study carried out on 10 students, in the pre-cycle activities the number of students who completed was 2 students (2%), while students who had not completed were 8 students (8%), with an average score of 69.4%. In cycle I, there was an increase in the number of students who completed 7 students (7%) while students who had not completed were 3 students (3%) with an average score of 75.9%. Then in cycle II, there was a very high increase compared to the previous cycle, namely students who had reached the KKM were 9 students (9%), while students who had not completed were 1 student (1%) with an average score of 77.8%. Conclusion: This study shows that the application of differentiated learning can improve the learning outcomes of Islamic Religious Education in class VII students of SMPN 35 (Berasrama) Kaur in the 2024/2025 academic year.